Expression of ER, PR and Ki-67 in tumor with different genetic variants of ESR and levels of antiidiotypic antibodies to steroid hormones in breast cancer patients - A. N. Glushkov; E. G. Polenok; L. A. Gordeeva; S. A. Mun; O. A. Glushkova; V. N. Zakharov; A. V. Antonov; P. V. Bayramov; N. E. Verzhbitskaya; E. N. Voronina; G. I. Kolpinskiy (Фундаментальная и клиническая медицина, 2024)
Aim. To study the possible associations of tumor ER, PR and Ki-67 expression with ESR1 and ESR2 genes polymorphisms and blood serum levels of antiidiotypic antibodies IgG2-E2 and IgG2-Pg in breast cancer patients (BCP).Materials and Methods. Blood serum levels of IgG2-E2 and IgG2-Pg were studied in 1025 BCP (478 with stage I and 547 with stages II-IV) by means of enzyme-linked immunosorbent assay. Real-time PCR was performed for ESR1(rs2234693) and ESR2 (rs4986938) genes polymorphisms detection. ER, PR and Ki-67 positive tumor cells was determined using immunohistochemistry.Results. IgG2-E2 and IgG2-Pg blood serum levels were not depended on ESR1 and ESR2 gene polymorphisms in BCP. ER+/PR+ tumors were revealed more frequently and ER-/PR- tumors less frequently in BCP at the I stage with high serum levels of both IgG2-E2 and IgG2-Pg than in BCP with their low levels: in patients with genotype TC ESR1 (91.8 % and 3.3 % vs 73.9 % and 11.1%, p = 0.015). Such differences were not revealed in patients with genotypes TT and CC ESR1. There were not discovered the desired association of ER/ PR tumor phenotype with studied antibodies and ESR2 genes polymorphisms. High levels of tumors Ki-67 positive cells (>20%) were determined less frequently in BCP at the II-IV stages with high levels of both IgG2-E2 and IgG2-Pg than in BCP with their low levels: in patients with genotypes TC ESR1 (48.4 % vs 69.7 %, p = 0.004) and GA ESR2 (46.8 % vs 66.3 %, p = 0.009). There were not revealed such differences in patients with other variants of ESR1 and ESR2 genotypes.Conclusion. Synergistic effects of IgG2-E2 and IgG2-Pg were discovered in BCP: the maintenance of ER and PR in tumors at the I stage and inhibition of tumor proliferation at the II-IV stages.